Src promotes cutaneous wound healing by regulating MMP-2 through the ERK pathway - WU, XUE (Int J Mol Med, 2016)
Wound healing is a highly orchestrated, multistep process, and delayed wound healing is a significant symptomatic clinical problem. Keratinocyte migration and re-epithelialization play the most important roles in wound healing, as they determine the rate of wound healing. In our previous study, we found that Src, one of the oldest proto-oncogenes encoding a membrane-associated, non-receptor protein tyrosine kinase, promotes keratinocyte migration. We therefore hypothesized that Src promotes wound healing through enhanced keratinocyte migration. In order to test this hypothesis, vectors for overexpressing Src and small interfering RNAs (siRNAs) for silencing of Src were used in the present study. We found that the overexpression of Src accelerated keratinocyte migration in vitro and promoted wound healing in vivo without exerting a marked effect on cell proliferation. The extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling pathways play important roles in Src-accelerated keratinocyte migration. Further experiments demonstrated that Src induced the protein expression of matrix metallopro-teinase-2 (MMP-2) and decreased the protein expression of E-cadherin. We suggest that ERK signaling is involved in the Src-mediated regulation of MMP-2 expression. The present study provided evidence that Src promotes keratinocyte migration and cutaneous wound healing, in which the regulation of MMP-2 through the ERK pathway plays an important role, and thus we also demonstrated a potential therapeutic role for Src in cutaneous wound healing.